Sentinelas poéticas: os elefantes de Drummond, Alvim e Chacal - Borsato, Fabiane Renata [UNESP] (My University, 2011)
This article aims to analyze the intertextuality, the dimension of passion, the modal existence of the paternal subjects, enunciators of the poems "The Elephant" (1945), by Carlos Drummond de Andrade, "Elephant" (2000), by Francisco Alvim and "Sentinel" (2005), by Chacal.

Este artigo pretende analisar a intertextualidade, a dimensão passional e a existência modal dos sujeitos patêmicos, enunciadores dos textos “O elefante” (1945), de Carlos Drummond de Andrade; “Elefante” (2000), de Francisco Alvim e “Sentinela” (2005), de Chacal.
Poetics sentinels: the elephants of Drummond, Alvim and Chacal
Keywords: Passions’s enunciation; Intertextuality; Carlos Drummond de Andrade; Francisco Alvim; Chacal; Enunciação passional; Intertextualidade; Carlos Drummond de Andrade; Francisco Alvim; Chacal